What are the perspectives of adolescents with Down syndrome about their quality of life? A scoping review. (14th November 2019) - Sheridan, Ciara; OMalley‐Keighran, Mary‐Pat; Carroll, Clare
Accessible summary: This study looked for information about the quality of life of adolescents with Down syndrome. We found two studies about quality of life that included the voice of the adolescent with Down syndrome. Most of the research includes parents' voices. Parents' views are important, but we need to also include adolescents with Down syndrome in research about their lives. Friends, family and independence are important to adolescents with Down syndrome. More information on quality of life is needed to help us understand more about their individual needs. Abstract: Background: There is a wealth of research on adolescents with Down syndrome (DS) covering a large range of topics such as obesity, speech and language, education and health‐related quality of life. However, for quality of life, much of the available literature for adolescents with DS relies on parent proxy reporting. This results in more research on parent's perspectives rather than from the individuals with DS themselves. Aim: This study aimed to examine the literature to identify the literature that included the voice of adolescents with DS in research about quality of life. It aimed to address the research question: What evidence exists in relation to the perspectives of adolescents with DS about their quality of life? Method: A scoping review allowed for an extensive range of research and nonresearch material to be gathered. Search terms were identified, followed by searches of five electronic databases, Google scholar and Lenus (Irish Health Repository). Two researchers conducted the review. Studies were selected through inclusion/exclusion criteria. A chart summarised information from the selected studies. Results: A total of 596 articles were marked for title and abstract screening. Forty‐five articles were included for full‐text review. Forty‐three of these met exclusion criteria, resulting in two articles which included the voices of adolescents with DS themselves. For adolescents with DS, participation socially and in their communities was important as well as friendships, family relationships and functional independence. These themes need to be further explored. Conclusion: The UN Convention on the Rights the Person with Disabilities argues strongly for participation (United Nations [2006], UN convention on the rights of persons with disabilities). This paper highlights the lack of and need for further empirical quality‐of‐life research with adolescents with DS from their own perspectives.